Outcome of Endovascular Procedure in Chronic Limb Ischemia Femoropopliteal Lesion: A Literature Review - Utama, Alexander J; Thio, Robby E (The New Ropanasuri Journal of Surgery, 2023)
Introduction. Angioplasty and stenting are the two main endovascular treatments for femoropopliteal lesions associated with chronic limb ischemia. To summarize the research in this area, this article examines the state of these treatments today, diving into clinical subtleties and new trends. The objectives was to thoroughly analyze the body of research, combining knowledge about the results of endovascular angioplasty and stenting. Methods: Literature was searched in some databases (Cochrane, PubMed, and EBSCO) from June to July 2021. Results: Five articles that met the inclusion and exclusion criteria were identified. There were two randomized control trials and three cohort studies. There was no difference in primary patency of balloon angioplasty and nitinol stenting on follow-up for five years. Amputation-free survival rates in the coated balloon and plain balloon groups were not different. Revascularization was also not significantly different in both groups. There was no complication reported in either group. Mortality rates in both groups were also not different after follow-up in 30 days. Conclusions: There were no notable variations in the results of endovascular angioplasty and stenting for femoropopliteal lesions associated with chronic limb ischemia